Reformulation of the Action and Phase Jump Method to Obtain Magnetic Errrors in the LHC (2015)
Abstract. a reformulation of the Action and Phase Jump method is presented, using orbits from simulations and from experiments at LHC. The new equations are central BPM independent and take into account the phase-advance for the quadrupoles at the triplets. Studies of digital-filters and the AC Dipole effect are included. Also, a comparison with the previous formulation and the alternative methods is presented.